Role of SiO₂ in the synthesis of Zn₂SiO₄ composite on physical, structural and optical properties - Che Engku Ali, Engku Abd Ghapur (2017)
Zinc silicate (Zn₂SiO₄), or willemite ceramic is an attractive material and has a wide range of applications. A lot of attention has been given to the synthesizing of Zn₂SiO₄ with better properties. This involves applying a new technique, or modifying existing methods. In this study, Zn₂SiO₄ composite-based ceramic was synthesised using amorphous SiO2 nanoparticles as a silicon source. The amorphous SiO2 nanoparticles were obtained from a simple precipitation process of preparing aqueous sodium silicate with ethanol at different reaction times. Different ratios of Zn:Si were prepared by mixing amorphous SiO₂ nanoparticles with aqueous zinc nitrate. Amorphous SiO₂ nanoparticles were encapsulated by the zinc source in aqueous solution, dried, and subjected to heat treatment. The produced SiO₂ nanoparticles were in amorphous form according to the XRD pattern. The range of particle size was between 63.5 ± 4.0 to 99.0 ± 3.1 nm, which increased with increasing reaction time. The sample with 90 minutes of reaction time showed fine pore characteristic, with the highest total pore volume of 0.4804 cm3g-1. This characteristic had significantly changed the optical properties of the final product. The heat treatment underwent by the amorphous SiO₂ nanoparticles, with zinc source mixture, showed the changing of phases, morphology, and size with increased temperature. During calcination, ZnO phase appeared at the beginning of heat treatment and Zn₂SiO₄ phase started to emerge at 800 °C onwards, as shown by XRD patterns. This observation is supported by the FTIR spectrum, which identified SiO₂, ZnO₄, and Zn-O-Si bands that referred to the Zn2SiO4 phase. Optical band gap analysis of Zn₂SiO₄ composite was determined to be within the range of 3.12 ± 0.04 to 3.19 ± 0.04 eV. The photoluminescence of treated samples showed emission peaks at 411 and 455 nm wavelengths from ZnO’s blue band and at 528 nm wavelength from Zn2SiO4’s green band. The availability of zinc ions on the surface and inner pore sites of the amorphous SiO₂ nanoparticles could have diffused and formed Zn₂SiO₄ during heat treatment at much lower temperatures. The diffusion of zinc ions into Zn₂SiO₄ composite with high surface area will favour the diffusion at a much lower temperature compared to a conventional solid state method. This optical characteristic is expected to be a potential candidate for applications using phosphor materials and in opto-electronic devices.